Indonesia’s Foreign Policy Strategy for Regional Security through the ASEAN Outlook on the Indo-Pacific - Saragih, Hendra Maujana; Salsabila, Jaisy Khailisah (Universitas Muhammadiyah Yogyakarta, 2026)
As geopolitical tensions increase in the Indo-Pacific region, Indonesia has created a security approach that does not rely on military alliances or regional blocs. Through the use of a constructivist approach and a qualitative descriptive method, including document analysis, this paper assessed Indonesia’s position in the ASEAN Outlook on the Indo-Pacific (AOIP). AOIP has been regarded as more than just a consensus among ASEAN member states; it is viewed as a strategic instrument that illustrates Indonesia’s role as a middle power. Based on the results of this study, it is clear that Indonesia views AOIP as a normative framework based on its independent and active foreign policy, inclusiveness, and the supremacy of International Law, specifically UNCLOS 1982. Unlike other tools adopted for power balancing, AOIP serves as a norm-building mechanism and supports ASEAN centrality while maintaining regional strategic autonomy. Through the use of AOIP’s four pillars of maritime cooperation, connectivity, sustainable development, and economic cooperation, Indonesia positions itself as a norm entrepreneur in the Indo-Pacific using its normative diplomacy, institutional leadership, and capacity building. This study contributes to constructivist scholarship by depicting how middle powers can affect the governance of regional security through ideational leadership despite structural competitive constraints.